Teacher Education in the 21st Century 2019
DOI: 10.5772/intechopen.83437
|View full text |Cite
|
Sign up to set email alerts
|

The Purposeful Teacher

Abstract: In this chapter, a purposeful teacher is introduced as a goal in teacher education for the twenty-first century. Purposeful teacher is defined as a teacher with moral purposes. Purposeful teachers are ethical professionals who have both freedom and responsibility to make pedagogical decisions in the best interest of their students. Purposeful teaching is discussed in the Finnish context with some examples of the current educational challenges. The purpose profiles of Finnish student teachers are presented to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 23 publications
0
7
0
1
Order By: Relevance
“…We also found that most of the descriptions of the students and the practising teachers were self-oriented, indicating that within Damon et al's [4] and Tirri's [1] framework these participants did not exhibit the purpose or the profile of a purposeful teacher. Further, for some the other-focus referred only to their own family.…”
Section: Discussionmentioning
confidence: 75%
See 4 more Smart Citations
“…We also found that most of the descriptions of the students and the practising teachers were self-oriented, indicating that within Damon et al's [4] and Tirri's [1] framework these participants did not exhibit the purpose or the profile of a purposeful teacher. Further, for some the other-focus referred only to their own family.…”
Section: Discussionmentioning
confidence: 75%
“…The changing situation in teacher education and the new demands of the 21st century call for teachers who find both a personal and a societal purpose in teaching, and who can commit to the teaching profession in the long term [1]. We propose purposeful teaching as a goal in teacher education to meet the challenges of the 21st century.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations